Persepsi Pengawas Terhadap Kinerja Guru SD di Kecamatan Sekongkang - Wahidin (Yayasan Pembina Lembaga Pendidikan (YPLP) PGRI Kabupaten Sumbawa Barat - NTB - Indonesia, 2022)
The general objective of this research is to obtain a clear picture of the supervisor's perception of teacher performance in the Sekongkang District. This study uses a descriptive research method with a qualitative approach, descriptive research is a method used to examine the problems that occur at the present time and aims to create an objective picture of a situation. Based on the results of the research, the supervisor's view or response to the teacher's performance is that the teacher must at least be a planner, where a teacher must have the ability to design learning that is appropriate and suitable for the conditions in the field, being a manager, the teacher must also be able to create a learning climate conducive environment so that students can learn well, while as an evaluator, the teacher must have the ability to assess the process and learning outcomes of students as a whole, besides that, the teacher must also have the ability and skill in using ICT in the learning process